The effect of natural antioxidants on long-term stability of sweet red pepper seed oil - Jasmina Ranilović; Tanja Cvetković; Irena Vađunec Bajrić; Vesna Kadija-Cmrk; Tihomir Moslavac; Marina Ilakovac Kveder; Dalibor Merunka; Jurica Jurec; Srećko Valić; Stela Jokić (Croatian Journal of Food Science and Technology)
Oils obtained from fruit and vegetable by-products represent a new category of niche oils. Cold-pressed oil from the seeds of sweet peppers of the Podravka and Slavonka varieties is a new, high-quality oil from the vegetable niche oil category, naturally rich in polyunsaturated linoleic fatty acid, γ-tocopherol, and sterols as antioxidants that exhibit positive effects on human health in preventing chronic non-communicable diseases. However, for a broader commercial reach of this oil, preserving its quality over a longer period is of utmost importance. Based on monitoring four parametres (peroxide value, free fatty acids, antioxidative power, and radical potential), pure pepper seed oil did not have adequate quality by the end of the period of 9 month stored at room temperature due to oxidative changes. The addition of natural antioxidants such as green tea extract (0.2%), especially rosemary extract (0.2%) and a blend of rosemary extract (0.2%), and citric acid (0.01%) extended the stability of pure pepper seed oil to a period of one year. Since oxidation affects the organoleptic quality and nutritional composition of the oil, these results are encouraging for niche oil producers, not only because of the expansion of this category of edible oils made from secondary source raw materials (by-products), but also because of the evidence that their special quality will not be compromised within the declared shelf life due to oxidative spoilage.